Multi-target combination treatment with rTMS and tDCS for Tourette syndrome: a case report - Zhao, Shuang; Jin, Qizu; Yang, Qi; Liu, Jing; Lu, Yun; Ai, Haibo (Frontiers in Human Neuroscience, 2025)
Tourette syndrome (TS) is a neuropsychiatric disorder characterized by chronic motor and phonic tics, with a higher prevalence among boys. This condition can significantly impact patients’ learning and daily life. Due to the limited efficacy and potential side effects of pharmacological treatments for TS, there is a critical need to develop novel, tailored therapeutic strategies. Repetitive transcranial magnetic stimulation (rTMS) and transcranial direct current stimulation (tDCS) have been proposed as potential treatments for TS, and have shown promising results. Here, we report a case of refractory TS, in which low-frequency rTMS was delivered to the left supplementary motor area (SMA), combined with tDCS targeting the primary motor cortex (M1) and the cerebellum, with the cathode positioned over the right M1 and the anode over the left cerebellum. This is the first reported case using a multi-target combination therapy for TS. This treatment yielded favorable outcomes and maintained good efficacy during a three-month follow-up period. Although larger-scale trials are needed, our findings pave the way for the application of non-invasive brain stimulation techniques in TS, offering a transformative path to improve treatment outcomes and quality of life for those with TS.